Discursive Colorlines at Work: How Epithets and Stereotypes are Racially Unequal. Issue 2 (28th February 2013) - Embrick, David G.; Henricks, Kasey
<x xml:space="preserve">Abstract</x> In a racialized social system, racial slurs and stereotypes applied to whites by nonwhites do not carry the same meanings or outcomes as they do when these roles are swapped. That is, racial epithets directed toward whites are unlikely to affect their life chances in the same way that racial epithets directed toward minorities do. Our central question in this paper is in what ways are epithets and stereotypes racially unequal? To answer this question, we rely upon a case study to drive our analysis. We argue that the symbolic meanings and outcomes of epithets and stereotypes matter because they maintain white supremacy in both material and symbolic ways. Thus, they serve as resources that impose, confer, deny, and approve other capital rewards in everyday interactions that ultimately exclude racial minorities, blacks and Latinas/os in particular, from opportunities and resources while preserving white supremacy.